2021
DOI: 10.1093/clinchem/hvaa248
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Detection of Clinically Relevant Mutations in Liquid Biopsies of Cancer Patients Using a Hybridization-Based Platform

Abstract: Background With the advent of precision oncology, liquid biopsies are quickly gaining acceptance in the clinical setting. However, in some cases, the amount of DNA isolated is insufficient for Next-Generation Sequencing (NGS) analysis. The nCounter platform could be an alternative, but it has never been explored for detection of clinically relevant alterations in fluids. Methods Circulating-free DNA (cfDNA) was purified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Clinical tests have been developed employing nCounter technology, including the FDA-approved nCounter Prosigna test, which stratifies breast cancer subtypes and predicts recurrence risk in post-menopausal women [27,28], and the tumor inflammation signature (TIS) assay, which forecasts PD-1 checkpoint blockade and clinical response across several tumor types [29]. This platform has also been employed for the discovery of potential biomarker signatures in various types of LB biosources, including cfDNA, cell-free RNA (cfRNA), EVs (including DNA, micro RNA (miRNA) and mRNA), as well as CTCs [30][31][32][33][34][35][36]. However, the platelet transcriptome has not been explored yet through this technology for LB purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical tests have been developed employing nCounter technology, including the FDA-approved nCounter Prosigna test, which stratifies breast cancer subtypes and predicts recurrence risk in post-menopausal women [27,28], and the tumor inflammation signature (TIS) assay, which forecasts PD-1 checkpoint blockade and clinical response across several tumor types [29]. This platform has also been employed for the discovery of potential biomarker signatures in various types of LB biosources, including cfDNA, cell-free RNA (cfRNA), EVs (including DNA, micro RNA (miRNA) and mRNA), as well as CTCs [30][31][32][33][34][35][36]. However, the platelet transcriptome has not been explored yet through this technology for LB purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been embraced in translational research, including the development and validation of liquid biopsies, due to its capability of working with a low quantity of highly degraded samples [ 15 , 16 ]. Recent studies reported the use of nCounter for the study of several categories of circulating biomarkers [ 17 , 18 , 19 , 20 , 21 ], including EV-derived DNA [ 22 ], miRNA [ 23 , 24 ], mRNA [ 25 ] and circRNA [ 26 ]. However, nCounter analysis of EV-circRNAs has not been investigated for early detection of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Samples previously evaluated for cyto-molecular NGS testing include FFPE cell blocks, ascites/ peritoneal washing supernatants, cell pellets, direct smears, cells scraped from slides, and additional aspirated samples (14)(15)(16). NGS analysis of FFPE cell blocks from two pancreatic cancer patients and supernatants of ascitic fluid from three gastric and one colon cancer patients showed concordant results with tissue samples (14,17). Other studies evaluated cell free DNA (cfNDA) from ascitic fluid and detected TP53, EGFR, ALK, BRAF from ovary and lung cancer patients using duplex sequencing or PNA-Q-PCR (18)(19)(20).…”
Section: Discussionmentioning
confidence: 92%